KONTRIBUSI BUDAYA ORGANISASI TERHADAP RESILIENSI PENGURUS HIMA JURUSAN ILMU PENDIDIKAN FKIP UNIVERSITAS RIAU - Suci Nasution, Raudya Nurul; Wilson, Wilson; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to see the contribution of organizational culture to the resilience of HIMA management. This research was conducted in the Dapartement of Education, FKIP Riau University. The variables used were organizational culture and resilience, measurement indicators in organizational, namely the behavior of organizational members, creativity behavior of organizational members, loyalty behavior of organizational members, measurement indicators in resilience, namely emosional regulation, control of impulses, optimism, ability analyzing cases, empathy, efficacy and achievement. The sample used ih this study amounted to 71 respondents, the method used ih this research is quantitative, the results obtained ih the study are the organizational culture level of the HIMA management ih the Dapartement of Education, FKIP Riau University is very high, the level of resilience of the HIMA management ih the Dapartement of Education, FKIP Riau University is very high, the contribution or organizational culture to the resilience of the HIMA management ih the Dapartement of Education, FKIP Riau University is very low.Key Words: Organizational Culture, Resilience